2016
DOI: 10.1007/s12199-016-0574-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, adverse health, and risk factors in association with sensory impairments: data from a prospective cohort study of older Japanese

Abstract: Sensory impairments, mainly of vision and hearing, are prevalent among the older adults, and are the leading causes of disability in people aged 60 years and above around the world. However, epidemiological data on sensory impairments (prevalence, association with adverse health outcomes, risk and preventive factors, etc.) in community-dwelling older people are sparse in Japan. Using data from the Kurabuchi Study, a community-based prospective cohort study of adults aged 65 years or older, the author and colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…To test this hypothesis, structural MRI data were acquired from healthy adults and then assessed using the Sensory Profile questionnaire. Previous studies have shown that older individuals exhibit a general decline in sensory abilities [Campbell et al, ; Michikawa, ; Schubert et al, ] and have lower scores on the Sensory Profile relative to younger subjects [Brown and Dunn, ]. Additionally, the gray matter volumes of early sensory regions in healthy older adults decrease with age [Lemaître et al, ; Potvin et al, ; Resnick et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, structural MRI data were acquired from healthy adults and then assessed using the Sensory Profile questionnaire. Previous studies have shown that older individuals exhibit a general decline in sensory abilities [Campbell et al, ; Michikawa, ; Schubert et al, ] and have lower scores on the Sensory Profile relative to younger subjects [Brown and Dunn, ]. Additionally, the gray matter volumes of early sensory regions in healthy older adults decrease with age [Lemaître et al, ; Potvin et al, ; Resnick et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde kırsal ve kentsel bölgedeki bireylerin fiziksel performans durumlarını karşılaştıran yeterli çalışmaya rastlanmadı. Bir çalışmada görme ve işitme bozukluklarının bireylerin sağlık durumları ile ilişkili olan bağımsız faktörlerden biri olduğu görülmektedir (28). Çalışmamızda kırsal bölgede yaşayan geriatrik bireylerin fiziksel performanslarının, kentsel bölgede yaşayan geriatrik bireylere göre daha düşük olduğu gözlemlendi.…”
Section: Yöntemunclassified
“…Hearing impairment is among the most important disabilities that hampers quality of life, by interfering with communication and conversation; decreasing cognitive function; and contributing to depression, loss of education, and employment opportunities, as well as social isolation, loneliness, and stigma [1][2][3]. As of 2019, approximately 1.57 billion people, equating to one in five of the global population, had hearing impairment [4].…”
Section: Introductionmentioning
confidence: 99%